(untitled) (American International Journal of Sciences and Engineering Research, 2020)
The current study had attempted to explore the effect of leadership on employee creativity in FM service providers in Oman. It emphasizes on mid-level managers, engineers, and supervisors of FM service organizations in Oman. The populace is around 20,000. As ﬁrms depend on employees to innovation, though, it is important to investigate factors that aﬀect the employee creativity. The author set a self-administered questionnaire which has been spread to discover the respondents of 320 managers as well as their workers from four FM service providers. To discourse this issue, we shot to ﬁnd hidden components that drive the connection between leadership and group level creativity and intrinsic motivation for the employee. The authors conducted the correlation and regression exploration which suggested that leadership has the emotional impact of the organization’s individual creativity, intrinsic motivation, and organization success. The outcomes of the current paper had suggested that leadership, being an influential motivational instrument that will enhance employee creativity, a motivation that leads to organizational success. The insinuations as well as confines of the current paper were additionally deliberated.